Implementation of Integrated Marketing Communication (IMC) In Higher Education as An Adaptive Move in The Era of Industrial Revolution 4.0: A Case Study in Manado State Polytechnic - Agung Stefanus Kembau; Vekky Supit; Cysca Langi (AIBPM Publisher, 2019)
Marketing concepts is considered to be applicable in non-profit organizations in achieving their social mission. Manado State Polytechnic (POLIMDO) as a nonprofit institution develop an integrated marketing communication strategy (IMC) as an adaptive step in the industrial revolution era 4.0. A sensitive organization community needs, which utilizes the media in conveying its values and identity as a vocational tertiary institution in North Sulawesi. This research provides an overview of the concept of customer-oriented in the perspective of nonprofit organizations, describe how the implementation of IMC in higher education institutions.